ПОНИМАНИЕ ПРОФЕССИИ В СОВРЕМЕННОЙ ПСИХОЛОГИЧЕСКОЙ ЛИТЕРАТУРЕ - Нурымбетова, Э.Ж. (SCIENCE and SOCIETY, 2021)
The article presents a theoretical overview of the problem of professional activity, which examines the understanding of the profession in contemporary psychological literature.